Formulação e estudo da citocompatibilidade de hidrogéis termossensíveis contendo partículas bioativas para aplicação em regeneração óssea - Novak, Sara (Universidade Federal de São Carlos, 2022)
Although the osteogenic properties, there are still some limitations to employing bioactive glasses (BG) in the human body, such as potential cytotoxicity and a lack of controlling the morphology of BG particles. Furthermore, particles presenting smaller sizes can be helpful for the preparation of organic-inorganic composites with improved properties. These composites have gained attention in the last years due to the possibility of employing them in bone regeneration. However, osteoporosis remains one of the most embracing pathologies in the world. In this research, a new material based on the thermosensitive Poly(N-vinilcaprolactam) (PNVCL) hydrogel and BG particles was developed as a candidate for bone regeneration. For that, BG-based particles were synthesized by melt-quenching and sol-gel methods, and milled to achieve submicron particles. These BG-based particles showed a bactericidal effect against Staphylococcus aureus and a relatively fast in vitro hydroxycarbonate apatite formation. Different amounts of these particles were then employed in the formulation of PNVCL hydrogels. The viscoelastic properties and cytocompatibility of the hydrogels were widely investigated. PNVCL syntheses were performed using ethanol, ethyl acetate, and DMSO to evaluate the effect of the solvent on the final characteristics of the polymers. The hydrogels exhibited a sol-gel thermosensitive transition close to the human body temperature offering the possibility of being injected. The entrapment of the BG-based particles in the PNVCL hydrogel showed to be beneficial for osteoblastic cells decreasing the cytotoxicity and resulting in cytocompatible composites. Furthermore, the rheological behavior of the composites could be adjusted by the type and amount of particles. These hydrogels have shown potential as an injectable biomaterial for a site bone remineralization.
Preparation and cytocompatibility of thermosensitive hydrogels containing bioactive particles for bone tissue regeneration
Keywords: Vidros bioativos; Regeneração óssea; Bioactive glasses; Thermosensitive hydrogel; Bone regeneration; Hidrogel termossensível; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::CERAMICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA